IoT based H-E-T Monitoring & Alerting System - Dhaval Patania, Mr.; Nisha Iyer, Ms.; Vivek Darji, Mr. (International Journal of Engineering and Technology, 2018)
When considering health, one of the most important parameter to be seen is the state of heart. The heart is the main element in a human body which is muscular organ about the size of a closed fist that functions as the bodyâ€™s circulatory pump. It takes in deoxygenated blood through the veins and delivers it to the lungs for oxygenation before pumping it into various arteries. There exists a project which can measure ECG (Electrocardiogram), temperature and heartbeat rate and the base of working was using Bluetooth (802.15.1), which passed the readings of the system to the Android and desktop application. The current project masks all the inabilities of the previous systems which it was supposed to cover. The current project is very synchronized version of the previous system created. It is compact, easy to use and cost friendly. This project will be working on Internet of Things (IoT), which uses Wi-Fi (802.11) for passing the readings of the system to the Android and desktop application. Wi-Fi enables the projectâ€™s abilities and the productivity to magnify at a high level.Â